2015
DOI: 10.1108/jfm-06-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

The workplace as a factor of job satisfaction and productivity

Abstract: Purpose – The purpose of this study is to examine degree of job satisfaction of the University of Athen’s (UOA) administrative staff, specifically regarding the workplace and its impact on their productivity. Design/methodology/approach – Questionnaires were distributed to 160 administrative personnel of the UOA. The study entails descriptive analysis, independent samples t-tests, ANOVA, Pearson correlations (two-tailed) and regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…Further, the co-workers are the most influencing factor of the job satisfaction while the working condition has been shown the lowest effect on job satisfaction. These findings were supported by the studies of Alam & Mohammad (2010), Deeba, Usmani, Akhtar, Zahra, & Rasool (2015) Kuria & Alice (2012) and Fassoulis & Alexopoulos (2015).…”
Section: Findings and Conclusionsupporting
confidence: 70%
“…Further, the co-workers are the most influencing factor of the job satisfaction while the working condition has been shown the lowest effect on job satisfaction. These findings were supported by the studies of Alam & Mohammad (2010), Deeba, Usmani, Akhtar, Zahra, & Rasool (2015) Kuria & Alice (2012) and Fassoulis & Alexopoulos (2015).…”
Section: Findings and Conclusionsupporting
confidence: 70%
“…However, Van der Voordt et al (2017, p. 67) concluded that "Although the relationship between employee satisfaction and labour productivity is not always statistically significant and can be interfered with by variables such as intrinsic motivation and competition with colleagues, various studies have confirmed that both constructs are correlated" (e.g. Zelenski et al, 2008;Halkos and Bousinakis, 2010;Fassoulis andAlexopoulos, 2015. De Been andBeijer (2014) found that satisfaction with the organisation plays a more substantial role in the perceived productivity support of the work environment, than the office concept.…”
Section: Interrelationships Between Productivity and Employee Satisfamentioning
confidence: 99%
“…Penelitian mengatakan bahwa kepuasan kerja berkaitan erat dengan pribadi karyawan sebagai cerminan perasaan seseorang terhadap pekerjaannya (Halkos, Bousinakis, Halkos, & Bousinakis, 2015). Sejalan dengan penelitian yang dilakukan oleh (Nikolaos, 2015) Peningkatan produktivitas kerja karyawan dapat dilakukan dengan berbagai cara, salah satunya memperbaiki lingkungan kerja menjadi lebih kondusif dan nyaman.…”
Section: Pendahuluanunclassified